Statistical modeling based fast rate distortion estimation algorithm for HEVC - Xiang MENG; Haibing YIN; Xiaofeng HUANG (Dianxin kexue)
To reduce the coding computational complexity of the rate and distortion calculations in HEVC, a fast TU level rate model with higher accuracy was proposed.The contribution percentages of different syntax elements in entropy coding were evaluated, and syntax element-wise accurate rate models were individually developed to construct the whole TU level model.In addition, coefficient levels were weighted adaptively to distinguish the nonuniform contributions of different coefficients in terms of rate profiling.Moreover, position-wise parameter was defined to depict the distribution patterns for possible non-zero coefficients within one block.The final linear rate model was developed by fine-tuning the model parameters from great amounts of samples in a statistical way.Finally, the transform domain distortion model was also established to bypass unnecessary reconstruction process.Experimental results show that the proposed algorithm can achieve 49.76% complexity reduction with 1.74% BD-BR increase for RA configuration.